FAST PATROL BOAT HULL DESIGN CONCEPTS ON HYDRODYNAMIC PERFORMANCES AND SURVIVABILITY EVALUATION - Pratama, Angga Sifta; Prabowo, Aditya Rio; Tuswan, Tuswan; Adiputra, Ristiyanto; Muhayat, Nurul; Cao, Bo; Hadi, Syamsul; Yaningsih, Indri (Journal of Applied Engineering Science, 2023)
A fast patrol boat is one of the ships intended to defend a region and rescue and search in the accident event so that the ship must have a high level of security and survivability performances. This study uses 9 design variations with various main dimensions and hull lengths to determine the effect of the different main dimensions on the hydrodynamic performances. Each criterion was affected to obtain results in hull design, durability, stability, seakeeping, floodable length, and motion sickness incidence (MSI). Simulations are carried out to determine the resistance, stability, ship response when exposed to external forces, passenger comfort, and ship safety level when a leak occurs. Resistance simulation uses a Froude number between 0 to 2.217. Stability simulation analyzes max GZ and angle of maximum GZ on seakeeping, deck wetness, and MSI simulations using 90°, 135°, and 180° wave incidence angles. The addition of bulkheads is carried out to determine the ship's response when it experiences a leak and prevents the ship's sinking when puddles enter the ship with five bulkheads per hull and three variations in distance. Design and simulation of various criteria using Maxsurf software. In the floodable length simulation, the hull added a bulkhead to determine the effect of leakage from several hull designs and watertight bulkhead spacing variations. Design 7 has the best average result compared to other designs from the simulation recapitulation results. It has a small resistance value, a large stability angle, a stable ship response when subjected to external forces, seasickness levels, and a small deck language. From the floodable length graph, it has a high flood limit that makes the ship survive and be safer than other designs. Design 7 refers to the ship Grandweld Shipyard Delivers 21M Discovery Class Vessel Fujairah Pilot.
Keywords: fast patrol boat, floodable length, bulkhead, survivability